Osteoimmunology : interactions of the immune and skeletal systems - Lorenzo, Joseph (Elsevier/Academic, 2011)
Bone and the immune system are both complex tissues, which, respectively, regulate the skeleton and the body's responses to invading pathogens. It has become increasingly clear that critical interactions between these two organ systems frequently occur. This is particularly true for the development of immune cells in the bone marrow and for the function of bone cells in health and disease. However, because these two disciplines developed independently, investigators in each don't always fully appreciate the significance of the other. This book is meant to provide a detailed overview of the many ways that bone and immune cells interact. The goal is to provide basic and clinical scientists with a better understanding of the role that the immune system and bone play in the development and function of each other so that advances in both fields will be facilitated. The focus of the book will be both on basic pathways and translational science, which will apply basic knowledge to clinical diseases. Chapter content will range from basic descriptions of the various cell systems and their development to the signals that cause them to interact during normal physiology and disease. Approximately half the book will focus on the role that osteoimmunology plays in the development of human diseases.